WEB-ДИЗАЙН ВА WEB - ДАСТУРЛАШ ФАНЛАРИДАН ЛАБОРАТОРИЯ ВА МУСТАҚИЛ ТАЪЛИМНИ ТАШКИЛ ҚИЛИШНИНГ ЗАМОНАВИЙ УСУЛ ВА ВОСИТАЛАРИ - Атаджанов, Х. (SCIENCE and SOCIETY, 2023)
The article is devoted to the organization of independent work of students on the subject of Web-technology and programming. Online systems are being studied for organizing students’ independent work.